The role of nesprins as multifunctional organizers in the nucleus and the cytoskeleton. (21st November 2011) - Noegel, Angelika A.; Neumann, Sascha
Abstract : Nesprins (nuclear envelope spectrin repeat proteins), also known as SYNE (synaptic nuclear envelope protein), MYNE (myocyte nuclear envelope protein), ENAPTIN and NUANCE, are proteins that are primarily components of the nuclear envelope. The nuclear envelope is a continuous membrane system composed of two lipid bilayers: an inner and an outer nuclear membrane. Nesprins are components of both nuclear membranes and reach into the nucleoplasm and the cytoplasm, where they undergo different interactions and have the potential to influence transcriptional processes and cytoskeletal activities.